True believer - Wolff, Virginia Euwer (London : Faber and Faber, 2001)
As a child life was easy but LaVaughn is 15 now and the obstacles aren't going away anymore. She has problems with her friends, her mother is distracted by a new man and the boy of her life pretends to be in love with her.
Keywords: Fiction -- Adolescense